2011
DOI: 10.1177/1932202x1102200205
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies Between Students' and Teachers' Perceptions of Homework

Abstract: For homework to help students improve school achievement and develop responsibility and autonomy in academic endeavors in and out of school, the development of teachers' understanding of students' views about homework and their homework behaviors is critical. Whether the subject of the homework is mathematics, reading, or a second language, teachers' and students' understandings regarding the types of problems that students experience during homework may differ. Discrepancies between students' and teachers' ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
1
30
0
5
Order By: Relevance
“…They reported that the assessment of students on homework behaviour is more negative evaluations. Hong et al (2011) observed that understanding the behaviour of students homework is important. They suggested that to reduce conflict and increase awareness of behavioural homework, the teacher should provide feedback and evaluate homework.…”
Section: Teachers Engagement In Mathematics Homeworkmentioning
confidence: 99%
“…They reported that the assessment of students on homework behaviour is more negative evaluations. Hong et al (2011) observed that understanding the behaviour of students homework is important. They suggested that to reduce conflict and increase awareness of behavioural homework, the teacher should provide feedback and evaluate homework.…”
Section: Teachers Engagement In Mathematics Homeworkmentioning
confidence: 99%
“…Students have more negative attitudes towards homework with lower motivation in general because they do not see the meaning of doing homework [40,41]. Homework-related stress has also come to some attention [42][43][44].…”
Section: Research In the Fieldmentioning
confidence: 99%
“…Bien qu'il n'y ait pas de consensus en faveur des devoirs et leçons, il s'agit d'une pratique omniprésente dans le système scolaire (Hong, Wan et Peng, 2011). Ce bref survol de l'évolution des devoirs et leçons au cours des derniers siècles permet de mettre en lumière combien cette pratique incarne une tradition du système scolaire.…”
Section: Les Devoirs Et Les Leçons : Entre Tradition Et Remises En Quunclassified
“…Comme mis en lumière par Hong, Wan et Peng (2011), en avançant en âge, la perception positive des devoirs et leçons a tendance à s'atténuer, plusieurs accordant de moins en moins de valeur intrinsèque et utilitaire à ces tâches. Parmi les quelques éléments de réponse fournis par les participants figurent, entre autres, le manque d'intérêt pour la nature et le type de travaux assignés, la durée et la complexité croissante de ces derniers et le manque de temps pour les loisirs qui en découle ainsi que le climat conflictuel à la maison qu'ils engendrent parfois.…”
Section: Oublis Et Persévérance Face Aux Devoirs Et Leçonsunclassified
See 1 more Smart Citation